2020
DOI: 10.32663/ba.v1i1.1152
|View full text |Cite
|
Sign up to set email alerts
|

Field-based investigation of aged biochar coupled with summer legumes effect on wheat yield in Pakistan

Abstract: There is a debate about whether the aged biochar effect can increase the crop yield or not. Herein, a field-based experimental data set and analysis provide the information on the aged biochar effect coupled with summer legumes on the yield of subsequent wheat. Briefly, in summer 2016, three different types of legumes i.e. mungbean, sesbania, and cowpea were grown with the intention of grain for human consumption, green manuring for soil fertility improvement, and fodder for livestock consumption. A fallow was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the fast growth stage, aged biochar research garnered remarkable attention and was extensively studied for various applications, including (1) the remediation of pollutants in soil and constructed wetlands (Khan et al, 2023), such as mercury (Zhang et al, 2019), aluminum, (Lin et al, 2018), cadmium (Jing et al, 2018), zinc (Kumar et al, 2018), copper (Gonzaga et al, 2020), lead (Raeisi et al, 2020), and herbicides (Gámiz et al, 2019b), (2) mitigation of greenhouse gases emissions such as nitrous oxide, carbon dioxide, and methane (Liao et al, 2021;Wang et al, 2021;Wu et al, 2019), (3) improved microbial and enzyme activities in soil (Yadav et al, 2019) and enhanced soil organic carbon content (Quan et al, 2020), and (4) nutrients availability and uptake by plants (Karimi et al, 2020) and ultimately, plant growth (Haider et al, 2015;Rahim et al, 2020). Wang et al (2024) conducted a pot experiment to explore the effects of fresh biochar (FBC) and freeze-thaw cycled aged biochar (FTC-BC) on di(2-ethylhexyl) phthalate (DEHP)-contaminated soils.…”
Section: Discussionmentioning
confidence: 99%
“…In the fast growth stage, aged biochar research garnered remarkable attention and was extensively studied for various applications, including (1) the remediation of pollutants in soil and constructed wetlands (Khan et al, 2023), such as mercury (Zhang et al, 2019), aluminum, (Lin et al, 2018), cadmium (Jing et al, 2018), zinc (Kumar et al, 2018), copper (Gonzaga et al, 2020), lead (Raeisi et al, 2020), and herbicides (Gámiz et al, 2019b), (2) mitigation of greenhouse gases emissions such as nitrous oxide, carbon dioxide, and methane (Liao et al, 2021;Wang et al, 2021;Wu et al, 2019), (3) improved microbial and enzyme activities in soil (Yadav et al, 2019) and enhanced soil organic carbon content (Quan et al, 2020), and (4) nutrients availability and uptake by plants (Karimi et al, 2020) and ultimately, plant growth (Haider et al, 2015;Rahim et al, 2020). Wang et al (2024) conducted a pot experiment to explore the effects of fresh biochar (FBC) and freeze-thaw cycled aged biochar (FTC-BC) on di(2-ethylhexyl) phthalate (DEHP)-contaminated soils.…”
Section: Discussionmentioning
confidence: 99%
“…Mungbean-wheat cropping system recorded higher values for yield and related traits, and grain protein content while sorghumwheat and fallow-wheat cropping systems recorded the lowest values of these traits at all locations (Tables 5, 6). Rahim et al (2020) reported that inclusion of restorative crops (legumes, i.e., pulses, peas, and beans) in cropping systems can improve soil fertility. The presence of mungbean in the mungbean-wheat cropping systems of the current study improved soil physical condition (Table 3) and nutrient availability (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Residual char from thermochemical processes (especially gasification) of lignocellulosic biomass, which contains ashes from original raw material and a carbonaceous residue forming a single solid material, can also be used for new applications, replacing little commercial materials which are not so environmentally friendly. Examples include using it as absorbent for metals in aqueous solutions [105] . Char from pyrolysis and gasification of RH is under study by the authors of this research paper as RH has a significant content of SiO2.…”
Section: Char Composition and Propertiesmentioning
confidence: 99%